The sorting of cargo proteins in the plant trans-Golgi network - Shimizu, Yutaro; Uemura, Tomohiro (Frontiers in Plant Science, 2022)
Membrane trafficking contributes to distinct protein compositions of organelles and is essential for proper organellar maintenance and functions. The trans-Golgi network (TGN) acts as a sorting station where various cargo proteins are sorted and directed to post-Golgi compartments, such as the multivesicular body or pre-vacuolar compartment, vacuoles, and plasma membrane. The spatial and temporal segregation of cargo proteins within the TGN, which is mediated with different sets of regulators including small GTPases and cargo adaptors, is a fundamental process in the sorting machinery. Recent studies with powerful imaging technologies have suggested that the TGN possesses spatially distinct subdomains or zones for different trafficking pathways. In this review, we will summarize the spatially and dynamically characteristic features of the plant TGN and their relation to cargo protein trafficking.